2015
DOI: 10.3991/ijep.v5i1.4046
|View full text |Cite
|
Sign up to set email alerts
|

Engaging High School Students in an Engineering Thermodynamics Project

Abstract: Abstract-Efforts for recruiting and retaining students in engineering programs are evident in many postsecondary institutions around the world. These efforts include outreach programs at both elementary and secondary school level, as well as projects that develop capacities beyond technical content-often taught as declarative and procedural knowledge. The mandate of the Galileo Education Network Association includes the design of rich learning environments engaging K -12 students in authentic tasks: tasks that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…To promote the professional development of foreign language teachers, it is necessary to create a good immersive virtual environment, improve teachers' recognition of learning performance [14][15][16], and improve the learning experience of students, so that teachers can actively teach and students can learn more actively [17][18][19]. The structure of the research context is shown in Figure 1.…”
Section: Research Situationmentioning
confidence: 99%
“…To promote the professional development of foreign language teachers, it is necessary to create a good immersive virtual environment, improve teachers' recognition of learning performance [14][15][16], and improve the learning experience of students, so that teachers can actively teach and students can learn more actively [17][18][19]. The structure of the research context is shown in Figure 1.…”
Section: Research Situationmentioning
confidence: 99%